2013
DOI: 10.3109/08820538.2013.833270
|View full text |Cite
|
Sign up to set email alerts
|

Macula and Retinal Nerve Fiber Layer in Migraine Patients: Analysis By Spectral Domain Optic Coherence Tomography

Abstract: The average RNFL thickness in the migraine patients was found to be thinner than that in the control group. In addition, we found a negative weak correlation between length of migraine history and the average RNFL thickness, supporting the possible association between these pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 23 publications
6
37
2
Order By: Relevance
“…It has been shown that RNFL thinning occurs at different quadrants, and there are also studies regarding the relation between migraine and retrobulbar blood flow alterations. [15][16][17][18][19][20][21] According to Kara et al, 30 the retrobulbar circulation and flow haemodynamics in the left vertebral artery may be altered in both headache and headache-free periods in migraineurs without aura. Glenn et al 31 reported a case of complicated migraine due to bilateral retinal infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that RNFL thinning occurs at different quadrants, and there are also studies regarding the relation between migraine and retrobulbar blood flow alterations. [15][16][17][18][19][20][21] According to Kara et al, 30 the retrobulbar circulation and flow haemodynamics in the left vertebral artery may be altered in both headache and headache-free periods in migraineurs without aura. Glenn et al 31 reported a case of complicated migraine due to bilateral retinal infarction.…”
Section: Discussionmentioning
confidence: 99%
“…2,[7][8][9][10][11][12][13][14] Also, there are studies supporting the ischaemic theory by focusing on the retinal nerve fibre layer (RNFL) thickness detected by optical coherence tomography (OCT) on migraine patients and studies demonstrating that the retina and cerebral structure of migraine patients are affected. [15][16][17][18][19][20][21] In the present study, we used OCT to determine whether RNFL thickness is related to the presence of cerebral WML in migraine patients. Thus, we aimed to evaluate an anatomical relationship of RNFL thickness to MRI findings in migraine patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these studies have additionally identified significant correlations between visual field loss and certain migraine features such as migraine frequency (De Natale et al, 1993;McKendrick and Badcock, 2004a;Nizankowska et al, 1997;Yenice et al, 2006), cumulative migraine history (McKendrick and Badcock, 2004a), and duration of worst headache (Harle and Evans, 2005), even if group differences in visual field performance were not found (Harle and Evans, 2005). Similarly, while there are no compelling group differences in structural retinal measures using the OCT, significant inverse relationships have been reported between retinal nerve fibre layer thickness and frequency of attacks (Martinez et al, 2009), duration of migraine history (Yulek et al, 2015), and severity of migraine (Martinez et al, 2009) as estimated by the Migraine Disability Assessment (MIDAS) questionnaire score (Lipton et al, 2001b;Stewart et al, 2001). These significant correlations raise the possibility that migraine may be associated with cumulative damage over time.…”
Section: Do Migraine Medications Affect Clinical Test Results?mentioning
confidence: 88%
“…In-built segmentation algorithms (Ishikawa et al, 2005;Tan et al, 2008) currently have the capacity to segment thickness measures into the following parameters: the macular retinal nerve fibre layer (mRNFL), the ganglion cell layer with inner plexiform layer (GCIPL) and the ganglion cell complex (mRNFL þ GCIPL), all of which have been useful in tracking longitudinal retinal structural changes in human glaucoma subjects (Bussel et al, 2014). Currently, the results of interictal macula imaging studies in migraine sufferers are inconclusive, with conflicting results of normal (Yulek et al, 2015) or reduced ganglion cell complex measures in people with migraine (Ekinci et al, 2014). Given that the functional data collected with perimetry can show improvement with time after a migraine (see Section 5.1.3), this predicts that the neural structure could be expected to remain normal with a gradual reduction in dysfunction after the headache.…”
Section: Macula Imaging In People With Migrainementioning
confidence: 98%
See 1 more Smart Citation